FLUCTUATING ASYMMETRY IN BRACHYPTEROUS AND MACROPTEROUS TRIATOMINE INSECTS FROM DIFFERENT GEOGRAPHIC ORIGINS (Boletín de la Sociedad Zoológica del Uruguay, 2025)
Triatoma guasayana is a triatomine insect vector of Trypanosoma cruzi, the etiological agent of Chagas disease. This study aims to evaluate changes in the fluctuating asymmetry (FA) of T. guasayana with wing polymorphism (Brachypterous-Macropterous) as an indicator of developmental instability, in order to estimate possible stressful environmental conditions during its morphogenesis. The work is based on the hypothesis that the geographic environment modifies the FA of heads, although this influence may vary to a greater or lesser extent depending on the brachypterous or macropterous condition. It is proposed here to determine whether the geographic environment or the wing condition has a stronger influence on the development of fluctuating asymmetry in heads. It was found that, in this triatomine, both the developmental environment and the wing condition (andpossibly flight activity) influence the increase in FA shape of head. Males and females show differences in the magnitude and direction of the changes observed in FA. The results obtained allow us to understand how the head phenotype can reflect the degree of adaptation to the environment and its implications for flight in a triatomine vector of a human parasitosis.
Keywords: Triatominae; Fluctuating asymmetry; geometric morphometrics; wing polymorphism